Complexation of a Polypeptide-Polyelectrolytes Bioparticle as a Biomaterial of Antibacterial Activity - Carlos A. B. Ramirez; Mateus M. Carriero; Fernanda S. C. Leomil; Ricardo L. Moro de Sousa; Antonio de Miranda; Omar Mertins; Patrick D. Mathews (MDPI AG, 2022)
The development of biomaterials to enable application of antimicrobial peptides represents a strategy of high and current interest. In this study, a bioparticle was produced by the complexation between an antimicrobial polypeptide and the biocompatible and biodegradable polysaccharides chitosan-N-arginine and alginate, giving rise to a colloidal polyelectrolytic complex of pH-responsive properties. The inclusion of the polypeptide in the bioparticle structure largely increases the binding sites of complexation during the bioparticles production, leading to its effective incorporation. After lyophilization, detailed evaluation of colloidal structure of redispersed bioparticles evidenced nano or microparticles with size, polydispersity and zeta potential dependent on pH and ionic strength, and the dependence was not withdrawn with the polypeptide inclusion. Significant increase of pore edge tension in giant vesicles evidenced effective interaction of the polypeptide-bioparticle with lipid model membrane. Antibacterial activity against Aeromonas dhakensis was effective at 0.1% and equal for the isolated polypeptide and the same complexed in bioparticle, which opens perspectives to the composite material as an applicable antibacterial system.